An Examination of Well-Being and Retention during the Transition of Learning Modality in a University Academic Department - Bardwell, Amy M.; Su-Russell, Chang (Teaching and Learning Inquiry, 2025)
The COVID-19 pandemic had an immediate impact and a long-lasting toll on the well-being of students and faculty, influencing their performance and affecting retention rates on college campuses. This study focused on the entire academic department, rather than an individual faculty member or peer, as the department serves as the immediate learning environment, potentially fostering diversity, equity, belonging, and inclusion (DEBI). The department is an academic home where students experience autonomy, relatedness, and competence. A total of 93 department members participated in a survey that elicited their perspectives and experiences related to retention, DEBI, and basic psychological needs during the first semester transitioning back from remote to in-person learning within the pandemic context. Results revealed that while the department is inclusive, there is room for improvement. Although many students and faculty/staff reported struggling during the transition, few expressed a decision to take a break from school/work. Students who were motivated to stay in school scored higher on departmental DEBI climate and basic psychological needs than those considering a break. Implications for department- and university-level policies and programs are discussed, focusing on addressing the well-being and retention of students and faculty/staff.